Analysis Of Project Failure Factors For Infrastructure Projects In Saudi Arabia: A Multivariate Approach - Ikediashi, Dubem I.; Ogunlana, Stephen O.; Alotaibi , Abdulaziz (Penerbit Universiti Sains Malaysia, 2014)
The rapidly changing face of the Saudi construction industry occasioned by the boost in oil revenue means that the best project management practices must be given priority to be able to confront the challenges associated with the management of infrastructure projects. The study develops a framework for identifying and classifying causes of project failures in the Saudi construction industry. A quantitative questionnaire survey was used to solicit responses from 67 respondents in the city of Jeddah, selected using an online questionnaire survey. Target respondents were mainly civil engineers, architects, quantity surveyors and building engineers who have years of experience in the management of infrastructure projects in Saudi Arabia. Findings reveal that poor risk management was rated the most critical failure factor for infrastructure projects, while budget overruns and poor communication by management followed closely at second and third, respectively. Additionally, eight components were extracted from the 24 items used for factor analysis. Among the extracted factors are project management deficiencies, risk challenges and government interference. Recommendations include, among others, that project risk management frameworks should be re-designed to guide clients and other stakeholders in an effort to reduce a project's unexpected exposure to risk.